2017
DOI: 10.1073/pnas.1701529114
|View full text |Cite
|
Sign up to set email alerts
|

Distinct conformations of GPCR–β-arrestin complexes mediate desensitization, signaling, and endocytosis

Abstract: β-Arrestins (βarrs) interact with G protein-coupled receptors (GPCRs) to desensitize G protein signaling, to initiate signaling on their own, and to mediate receptor endocytosis. Prior structural studies have revealed two unique conformations of GPCR-βarr complexes: the "tail" conformation, with βarr primarily coupled to the phosphorylated GPCR C-terminal tail, and the "core" conformation, where, in addition to the phosphorylated C-terminal tail, βarr is further engaged with the receptor transmembrane core. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
308
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(358 citation statements)
references
References 35 publications
20
308
1
4
Order By: Relevance
“…Active conformation of the receptor and subsequent GRK-mediated phosphorylation are generally thought to be prerequisite for β-arrestin binding (16), suggesting that the two main interactions occur simultaneously. Recent studies have shown that the phosphate and the core interactions can be separated in vitro or by using receptor chimeras and mutants (51)(52)(53). However, the question remained whether the distinct interactions could be independent in physiologically relevant situations.…”
Section: Discussionmentioning
confidence: 99%
“…Active conformation of the receptor and subsequent GRK-mediated phosphorylation are generally thought to be prerequisite for β-arrestin binding (16), suggesting that the two main interactions occur simultaneously. Recent studies have shown that the phosphate and the core interactions can be separated in vitro or by using receptor chimeras and mutants (51)(52)(53). However, the question remained whether the distinct interactions could be independent in physiologically relevant situations.…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated how GPCR core engagement affects the activation of β-arrestin trafficking by focusing on a polar region in β-arrestin that is located proximal to the conserved finger loop and is thought to directly contact the ligand-activated GPCR core 12,14 . We identified three charged residues in this ‘finger loop proximal’ region that produce constitutive β-arrestin-2 accumulation in CCSs when mutated to alanine (R77A, K78A, D79A; Figure 3a, b).…”
Section: Activation By Gpcr Core Interactionmentioning
confidence: 99%
“…A long-standing view is that all of these functions occur from a stable and stoichiometric GPCR/β-arrestin complex whose formation requires binding of the phosphorylated GPCR tail 7,8 . Emerging evidence suggests that GPCR/β-arrestin complexes can vary in structure but, nevertheless, all present concepts of cellular β-arrestin function require formation of a GPCR/β-arrestin complex driven by the phosphorylated GPCR tail 10,1417 .…”
mentioning
confidence: 99%
“…7,8 It has been suggested that these are in turn mediated by two distinct sites on arrestins -a 'phosphorylation sensor' and an 'activation sensor'. 3 In the past, studies have largely focused on activation of arrestins by the R P -tail and its functional outcomes, 9 while the role of the receptor transmembrane core, if any, has remained obscure. However, the two new papers illuminate the distinct roles of both the R P -tail and the 7 TM core in mediating arrestin interaction with and activation by GPCRs.…”
Section: 3mentioning
confidence: 99%